(3x+1)(8x-7)-(4x-1)(6x-3)=15
(x-4)(2x^2-3x+5)+(x2-5x+4)(1-2x)=20

Пепечка Пепечка    2   06.02.2022 19:55    0

Ответы
RitaMur RitaMur  06.02.2022 20:00

1) х=5

2)х=9

Пошаговое объяснение:

1)

24x {}^{2} - 21x + 8x - 7 - (24x {}^{2} - 12x - 6x + 3) = 15 \\ \\ 24x {}^{2} - 21x + 8x - 7 - (24 {}^{2} - 18x + 3) = 15 \\ \\ 24x {}^{2} - 21x + 8x - 7 - 24 x{}^{2} + 18x - 3 = 15 \\ \\ 5x - 10 = 15 \\ \\ 5x = 15 + 10 \\ \\ 5x = 25 \\ x = 5

2)

2x {}^{3} - 3x {}^{2} + 5x - 8x {}^{2} + 12x - 20 + x {}^{2} - 2x {}^{3} - 5x + 10x {}^{2} + 4 - 8x = 20 \\ \\ 0 + 4x - 16 = 20 \\ \\ 4x - 16 = 20 \\ 4x = 20 + 16 \\ 4x = 36 \\ x = 9

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика